Assessment of the semen of common carp males (Cyprinus carpio) induced with Ovaprim and (CPG) during propagation processes - Al Zaidy, Faleh M.; Al-Noor, Sajed S.; Al- Mukhtar, Mustafa A . (Iraqi Journal of Aquaculture, 2022)
The biological aspects for the semen of males (Cyprinus carpio) were assessed during the spawning season, after they were artificially induced for spawning. The males were induced for insemination by injecting with Ovaprim and pituitary gland extract. Two dosages had been used 0.5, 0.3 ml and 2,4 mg per Kg of body weight respectively. After that the volume of semen, pH, number of sperms in one ml and motility were estimated. The total volume of semen obtained from males ranged between (72 – 117) ml by using Ovaprim and pituitary respectively. while the average concentration of sperms changed between (35.3 ± 9.1)×109 sperm /ml to (28.2 ± 5.2)×109 sperm /ml for the Ovaprim and PG respectively. The mean of Spermatocrite value was (65.3 ±15.8) % for Ovaprim and (52.33 ±10.4) % for PG. The average motility of sperm fluctuated between (90 ±10) % and (95.4 ±5.6) % for semen was obtained from males injected by Ovaprim and pituitary respectively. The effectiveness period of sperms ranged between (101± 30.9) sec and (113±34.2) sec for the two hormones respectively. This study indicated that the males in this range of length and weight had semen suitable for the hatchery requirements.